Pendekatan Sel Sedimen untuk Analisa Perubahan Garis Pantai di Kecamatan Kaliwungu dan Kecamatan Brangsong, Kabupaten Kendal - Setiaji Bismoko; Warsito Atmodjo; Adi Santoso (Journal of Marine Research, 2012)
The purpose of this research is to study sediment cells to analyze the influence of sediment transport along the coast towards shoreline change, and know the area with erosion and accretion occur along the coast of Kaliwungu Subdistrict and Brangsong Subdistrict, Kendal Regency. The method used to determine the cell sediment is a remote sensing image interpretation and field survey by identifying sources of sediment, the sediment movement and sediment movement limits. The area that experiencing erosion and accretion is obtained from Landsat satellite image overlay. Satellite imagery used in this study is Landsat satellite image recording in 1991, 2001 and 2011. Barangsong Subdistrict and Kaliwungu Subdistrict in year 1991 until 2011 experienced eroded by 8,15 ha and 9,33 ha of accretion. The phenomenon of erosion and accretion in the subdistrict Barangsong and subdistrict Kaliwungu influenced by the source of sediment from the Blorong river, Waridin river, and Sapen river that serve as fixed limits in the concept of sediment cells. Coastline changes that occur in the study area is also due to reclamation that juts into the sea like jeti development and KLI (Kayu Lapis Indonesia).